Isquemia miocárdica em assintomáticos submetidos à ecocardiografia sob estresse pelo esforço físico - Barbosa, Igor Lobão (2015)
Background: Myocardial ischemia occurs in asymptomatic patients with no history of coronary artery disease (CAD). The physical stress echocardiography (PSE) is a good accurate diagnostic method. Coronary angiography (CATE) is of indispensable for the diagnosis and management of patients with coronary artery disease (CAD). Objective: Evaluate the differences in the presence or absence of atherosclerotic lesions in the CATE positive asymptomatic for myocardial ischemia to PSE; Define the predictors of the presence of atherosclerotic plaques in this group. Methods: Observational, cross-sectional analytical study with 278 asymptomatic patients who underwent EPS and CATE between 01/01/2000 to 12/31/2012 divided into two groups: Cate with lesions (WL), normal Cate (NC). The sample was not randomly chosen patients consecutively. Quantitative variables were compared by student t test and chi-square for categorical; analyzed the independent predictors of atherosclerotic lesions by logistic regression and considered significant p <0.05. Results: The WL was composed of 233 (83.3%) patients and NC for 45 (16.2%); the average age was higher (p <0.001) in WL (60.9 ± 9.56 years vs 51.8 ± 10.05 years). The WL group was older (60.9 vs 51.8 ± 9:56 ± 5.10, p <0.001), males (72.1% vs 53.3%, p = 0.01), hypertension (65.2% vs 48 , 9%, p = 0.03) and dyslipidemia (77.3% vs. 57.8%, p = 0.006) .The NC group showed more obesity (33.3% vs 14.2%, p = 0.002) and BMI (26.7 ± 3.73 vs. 29.06 ± 4.7, p = 0.003). Multivariate analysis showed that the independent predictors of CAD were age, male and fixed type of ischemia. Obesity behaved as a protective factor for atherosclerotic lesions in this study. Conclusions: The atherosclerotic plaque predictors of ischemic asymptomatic physical stress echo were age, male and fixed type of ischemia.